2016
DOI: 10.1590/1807-55092016000100079
|View full text |Cite
|
Sign up to set email alerts
|

Injuries prevalence in elite male artistic gymnasts

Abstract: The purpose of this study was to investigate the injuries prevalence in men elite artistic gymnasts. Twenty Brazilian senior gymnasts, aged 23.1 ± 6.5 years, 13.9 ± 5.0 years of practice and 36.5 ± 4.7 hours per week training, participated in this study. The athletes answered a morbidity questionnaire, formulated according to studies from the literature, for information on the injuries’ characteristics and circumstances. Information about the injury circumstances (gymnastic apparatus, overload training and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, previous studies have shown that 57% of injuries are overuse injuries (Paxinos et al, 2019), showing the risk associated with the frequent repetition of movements placing high stress on the lumbar spine. Previous studies have also shown that the floor is the apparatus with the highest injury prevalence in male artistic gymnastics (MAG) (Goulart et al, 2016;Kruse & Lemmen, 2009), involving both lower and upper extremity impacts as well as frequent hyperextensions and hyperflexions of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that 57% of injuries are overuse injuries (Paxinos et al, 2019), showing the risk associated with the frequent repetition of movements placing high stress on the lumbar spine. Previous studies have also shown that the floor is the apparatus with the highest injury prevalence in male artistic gymnastics (MAG) (Goulart et al, 2016;Kruse & Lemmen, 2009), involving both lower and upper extremity impacts as well as frequent hyperextensions and hyperflexions of the spine.…”
Section: Introductionmentioning
confidence: 99%